Implementasi Program Adiwiyata Melalui Pembelajaran Lingkungan Hidup Di Sekolah Dasar Al Muslim Wadung Asri Waru Sidoarjo - Budi Purwantiningsih; Asnal Mala (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The Adiwiyata is a program of the Minister of the Environment (KLH) with the Minister ofNational Education (Depdiknas) which aims to strive for how a love of the environment canbe used as an educational content for students from an early age in formal education. One ofthe schools that has implemented the Adiwiyata program through its learning is the Al MuslimWaru Sidoarjo School. The objectives of this study include: Knowing the application ofenvironmental learning through the Adiwiyata Program. (2) Knowing the Al Muslimelementary school curriculum. (3) Knowing the inhibiting factors in the implementation ofenvironmental learning through the Adiwiyata Program. This study uses a qualitative method.The research location was at Al Muslim Elementary School, Jl.Raya Wadung Asri 39F, WaruDistrict, Sidoarjo Regency. Data collection tools used in this study were interviews,documentation, and observation. The technique used is source triangulation starting from datacollection, data reduction, data presentation and drawing conclusions. The results showed that1) The application of environmental learning through the Adiwiyata Program was carried outwith a school culture transformation strategy and habituation through three activities namelyroutine, programmed, and spontaneous activities carried out by the Al Muslim ElementarySchool in collaboration with outside parties. 2) The curriculum used is the SuperiorCurriculum, Green Environment which is a monolithic and integrated, both in theory andpractice. 3) The obstacle faced in the implementation of environmental learning is theexistence of new educators, the time allotted, green land which is still minimal when comparedto the ratio of students of Al Muslim Waru Sidoarjo Elementary School.Keywords: Implementation, Adiwiyata, Green Environment